1984
DOI: 10.1002/cne.902250304
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of acetylcholinesterase in the hippocampal formation of the monkey

Abstract: In order to study the distribution of acetylcholinesterase (AChE) in the primate hippocampal formation, we have stained serial sections through the brains of nine macaque monkeys for AChE by two variants of the Koelle acetylthiocholine method. We have found a distinctive pattern of staining in the hippocampal formation which varies in intensity both from region to region, and along rostrocaudal and radial gradients within each region. In the dentate gyrus, there is intense staining of the inner one-third of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
1
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 40 publications
10
69
1
1
Order By: Relevance
“…In contrast. Bakst and Amaral [1984) demon strated that the density of AChE-eontaining fibers in the inner one-third of this layer in the monkey was obviously higher than that in the outer two-thirds. In addition.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast. Bakst and Amaral [1984) demon strated that the density of AChE-eontaining fibers in the inner one-third of this layer in the monkey was obviously higher than that in the outer two-thirds. In addition.…”
Section: Discussionmentioning
confidence: 97%
“…In guinea pigs, the superficial third of the layer stains very intensely, whereas the widest, intermediate part stains only weakly. Still other patterns of lamination have been observed in the dentate areas of ferrets [10], cats [27], macaque monkeys [1,31] and humans [23]. Only in mice [30] has a staining pattern been observed that roughly seems to correspond to that found in European hedgehogs.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the distribution of cholinergic elements in the medial cortex in reptiles is species-specific [Re gidor and Poch, 1988]. A comparable hypothesis has been put forth for the dentate area in mammals [Bakst and Amaral, 1984;Geneser, 1987],…”
Section: Cortexmentioning
confidence: 92%